KAJIAN TAFSIR ALQURAN DI FAKULTAS USHULUDDIN DAN HUMANIORA IAIN ANTASARI (REFLEKSI ATAS SKRIPSI MAHASISWA JURUSAN ILMU ALQURANDAN TAFSIR TAHUN 1993—2014) - Basrian, Basrian (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2017)
The effort to study and explore the meaning of the Quran has been done by Muslims through various approaches of knowledge, among others by interpreting methodologically as many previous mufassir done, such as ijmali method, tahlili, maudhui, and muqaran. This method is also applied (developed) at the level of educational institutions in the Department of Qurâanic and Tafsir Studies, Faculty of Ushuluddin and Humanities IAIN Antasari. Based on the results of studentsâ research, Â this study provides an indication that the themes of Quranic commentary studies show many variations, especially in the application of the developed interpretation methodology.